Methodological decisions and their impacts on the perceived relations between school funding and educational achievement - Shero, Jeffrey A.; Hart, Sara A. (Frontiers in Education, 2022)
Use of quantile regression, analysis at different levels of aggregation, and inclusion of covariates were used to assess how different methodologies produced varying results with contradictory implications for policy interventions regarding the relation between school funding and achievement. Results indicated that significantly different relations existed at various quantiles of the distribution of achievement, both for student and school-level outcomes. Further, significant differences were found when outcomes at the school-level were compared to outcomes for individual students. Finally, the inclusion of SES drastically altered the results of every analysis in this study, indicating the importance of controlling for confounds. Taking all of these findings into account, we find that higher levels of funding at the student-level were associated with smaller gaps in growth in achievement by SES for lower achieving students. The opposite finding was found at the school level, with higher levels of funding at the school level being associated with larger gaps in growth in achievement based on SES. We compare our findings to results of existing studies, framing our results and interpretations thereof in weighted-student funding literature. Discussion on how these findings can be translated into quasi-experimental research designs are also included.